Does Islam act as the 'Religious Motivation' for the radical Islamic suicide bombers such as the Hamas? - Teo, Eng Kee. (2008)
An alternative explanation of grievances for radical Islamic suicide terrorism when Islamism ideology cannot explain it. These grievances include history, poverty, humiliation and powerlessness. General recommendations are also suggested to nip the roots at its bud.